An Aggressive Clinical Presentation of Familial Leiomyomatosis Associated with a Fumarate Hydratase Gene Variant of Uncertain Clinical Significance - Federica Scarfi; Ana Paula Orozco; Alessia Visconti; Veronique Bataille (Medical Journals Sweden, 2020)
Abstract is missing (Short Communication)